Application of Ergonomic Exercise to Reduce Blood Pressure in Erderly Patiens with Hypertension in the Working Area of Simpang Tiga Public Health Center Pekanbaru (JONAH : Journal of Nursing and Homecare, 2026)
Hypertension is a common health problem among the elderly that may lead to serious complications. Ergonomic exercise is a non-pharmacological intervention involving safe, age-appropriate physical movements aimed at lowering blood pressure. This community service aimed to describe the application of ergonomic exercise to reduce blood pressure in elderly individuals with hypertension in the Tenayan Raya Public Health Center area, Pekanbaru. The method was used homecare, individual teaching; education and demonstration to erderly with hypertension. The intervention consisted of four sessions over two weeks, each lasting 30 minutes. Data were collected through interviews, observation, and blood pressure measurements before and after the intervention. The results showed a decrease in blood pressure. In conclusion, ergonomic exercise effectively reduced blood pressure in elderly patients and could serve as a simple, non-pharmacological intervention that can be implemented independently in communities and primary healthcare settings.